Purification of the water environment from ammonium nitrogen during nitrification in natural reservoirs and in water use facilities - Iurchenko, Valentyna; Ugnenko, Ievgeniia; Melnikova, Oksana; Sorokina, Kateryna (International Conference “Environmental Engineering”, 2023)
Nitrification are two unique reactions of sequential oxidation of ammonium nitrogen, carried out by chemolithoautotrophic bacteria and archaea. Establishing the main source of nitrification in aquatic ecosystems is necessary to manage this process. In experimental researches it has been established that in natural water bodies with a low technogenic load, nitrification is caused by processes in bottom sediments, in areas of water bodies after wastewater discharge – by processes in the water column. In technogenic environments (water use facilities) nitrification is caused by processes in solid phases (filter fillings and activated sludge). Nitrification activity of activated sludge in treatment facilities with deep biological treatment is high and the discharge of deeply purified wastewater into natural water bodies leads to an increase in the processes of nitrification and the activity of self-purification from nitrogen compounds in them.
Keywords: nitrification; phases of the aquatic ecosystem; natural reservoirs; water treatment systems; biological treatment facilities